2010
DOI: 10.1097/ajp.0b013e3181f18c36
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial Trigger Points in Neck and Shoulder Muscles and Widespread Pressure Pain Hypersensitivtiy in Patients With Postmastectomy Pain

Abstract: Our findings revealed bilateral widespread pressure pain hypersensitivity in patients with postmastectomy pain. In addition, the local and referred pain elicited by active TrPs reproduced neck and shoulder/axillary complaints in these patients. These results suggest peripheral and central sensitization in patients with postmastectomy pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 45 publications
3
70
1
2
Order By: Relevance
“…It has been suggested that reduction in COMT activity associated with the Met allele at codon 158 leads to a reduction in the content of encephalin (endogenous opioid-like peptides) in some regions of the central nervous system associated with the pain experience [7]. This hypothesis may be related to the presence of central nervous system hypersensitivity previously reported in breast cancer survivors [16][17][18][19]. A second mechanism can be that reduced COMT gene activity would result in elevated levels of catecholamimes, such as epinephrine, which promote the production of persistent pain states via the stimulation of b2-adrenergic receptors in the peripheral and central nervous systems [29].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has been suggested that reduction in COMT activity associated with the Met allele at codon 158 leads to a reduction in the content of encephalin (endogenous opioid-like peptides) in some regions of the central nervous system associated with the pain experience [7]. This hypothesis may be related to the presence of central nervous system hypersensitivity previously reported in breast cancer survivors [16][17][18][19]. A second mechanism can be that reduced COMT gene activity would result in elevated levels of catecholamimes, such as epinephrine, which promote the production of persistent pain states via the stimulation of b2-adrenergic receptors in the peripheral and central nervous systems [29].…”
Section: Discussionmentioning
confidence: 90%
“…The reliability of pressure algometry has been found to be high (ICC: 0.91, 95% CI 0.82-0.97) [25]. PPT levels were bilaterally assessed over the C5-C6 zygapophyseal joints, the deltoid muscle, the second metacarpals, and the tibialis anterior muscles according to previous studies [18,19] by an assessor blinded to the Val158Met polymorphism genotype of the participants.…”
Section: Pressure Pain Thresholds (Ppt)mentioning
confidence: 99%
See 1 more Smart Citation
“…134,135 Trigger points are peripheral sources of persistent nociceptive input, which can excite muscle nociceptors. 4,57,63,65,[136][137][138][139] Nociceptive input from muscle is particularly effective in inducing neuroplastic changes in the spinal dorsal horn and likely in the brainstem. 140,141 Dry needling may be instrumental in reversing such neuroplastic changes by removing a constant and intense nociceptive source.…”
mentioning
confidence: 99%
“…Por otro lado, existen estudios previos que han demostrado la existencia de una relación entre el dolor crónico en cáncer y una hiperalgesia muscular a la presión dolorosa en personas que han sobrevivido al cáncer de mama 20 Valoración de la calidad de vida, el estado musculoesquelético 3 que existe una hiperalgesia muscular al dolor a la presión generalizada y un aumento del dolor en la zona lumbar, a los 6 meses de una colectomía parcial 19 . Esto indica que podrían existir unos mecanismos de sensibilización tanto periféricos como centrales en este tipo de población.…”
Section: Introductionunclassified